Impact of Different Types of Cognitive Load in Foreign Language Learning - Zheng Haiyao; Noor Dayana Abd Halim (Environment and Social Psychology, 2026)
Cognitive load plays a critical role in foreign language learning, impacting the effect of learners' language acquisition. Various aspects of learners and instruction can influence different types of cognitive load. However, existing research on cognitive load in foreign language learning lacks a comprehensive review that categorizes and examines these different types of cognitive load. This literature review examined the factors contributing to intrinsic, extraneous, and germane cognitive load and the impacts of these three types of cognitive load in foreign language learning. Research revealed that the elements, such as the complexity of language materials, instructional design flaws, and motivational factors, significantly impacted cognitive load in foreign language learning contexts. A thorough understanding of these types of cognitive load and their impacts may inform effective instructional design, reduce unnecessary cognitive strain, and enhance foreign language acquisition. This review concluded by identifying gaps in current research and proposing suggestions to optimize cognitive load for further studies in foreign language education.